Pengembangan Produk Chocolate Cornnut sebagai Upaya Peningkatan Nilai Ekonomi Pangan Lokal - Dini Apriliani; Irma Yunita; Alvina Juliani Bahri; Karyadi Hidayat (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Although corn is an important food product in Indonesia, its unprocessed form still has low economic value. Public interest in traditional cuisine has also declined as a result of globalization, making innovation necessary to increase the appeal and added value of corn. Inspired by the traditional snack awuk-awuk, this research created Chocolate Cornnut, a corn-based innovation. The research method uses a mixed descriptive and simple experimental approach to describe the innovation process and determine the appropriate product formulation. The findings of this research indicate that Chocolate Cornnut can increase the added value of corn, enhance consumer appeal by combining traditional and contemporary flavors, and provide new business opportunities forUMKM. Beside external elements like the market, competition, and government policy support, internal factors such as human resources, management, finance, and technology also impact the success of product development. This product has the potential to preserve the sustainability of traditional cuisine while also evolving into a new and competitive local dish